2022
DOI: 10.3390/microorganisms10030575
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of Enterobacter sp. FY-07 as Kosakonia oryzendophytica FY-07 and Its Potential to Promote Plant Growth

Abstract: Precise classification of bacteria facilitates prediction of their ecological niche. The genus Enterobacter includes pathogens of plants and animals but also beneficial bacteria that may require reclassification. Here, we propose reclassification of Enterobacter FY-07 (FY-07), a strain that has many plant-growth-promoting traits and produces bacterial cellulose (BC), to the Kosakonia genera. To re-examine the taxonomic position of FY-07, a polyphasic approach including 16S rRNA gene sequence analysis, ATP synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The in vitro test on Jensen's nitrogen free media showed that the new bacterial isolate could grow on Jensen's medium and was acid producer. This agrees with [47] who suggested that Kosakonia sp. was an associative nitrogen-fixing bacteria or endophytic nitrogen-fixing bacteria.…”
Section: In Vitro Assessment Of Plant-growthpromoting Activitiessupporting
confidence: 92%
See 1 more Smart Citation
“…The in vitro test on Jensen's nitrogen free media showed that the new bacterial isolate could grow on Jensen's medium and was acid producer. This agrees with [47] who suggested that Kosakonia sp. was an associative nitrogen-fixing bacteria or endophytic nitrogen-fixing bacteria.…”
Section: In Vitro Assessment Of Plant-growthpromoting Activitiessupporting
confidence: 92%
“…This agrees with [51] who proved that pH decrease resulting from the release of organic acids could be related to P & K solubilization. These PGP activities may be due to sharing the bulk of genes that involved in plant growthpromotion as indicated with [47] who found that there were many genes related to promoting plant growth in Enterobacter FY-07.…”
Section: In Vitro Assessment Of Plant-growthpromoting Activitiesmentioning
confidence: 89%
“…Genus Kosakonia , designated in 2013 after reassignment of four species of Enterobacter ( 1 ), currently comprises at least nine species ( 2 ). These include K. sacchari , first isolated from Saccharum officinarum ( 3 , 4 ); and, K. pseudosacchari , found as a Zea mays endophyte ( 5 ).…”
Section: Announcementmentioning
confidence: 99%
“…In 2016, the Enterobacteriaceae faced taxonomic amendments when whole genome phylogeny was used to propose the order Enterobacterales and subdivide it into seven distinct families, namely Budviciaceae, Enterobacteriaceae, Erwiniaceae, Hafniaceae, Morganellaceae, Pectobacteriaceae and Yersiniaceae [1]. Since then, the family Enterobacteriaceae has undergone further taxonomic revision [2][3][4][5] and currently consists of 37 genera according to the List of Prokaryotic Names with Standing in Nomenclature [6]. Despite some exceptions, most members of the family are motile, catalase positive and oxidase negative.…”
Section: Introductionmentioning
confidence: 99%